2020
DOI: 10.2147/cia.s237505
|View full text |Cite
|
Sign up to set email alerts
|

<p>Higher Normal Levels of Triglyceride and Low and High-Density Lipoprotein Cholesterol Might Have a Protective Effect Against Activities of Daily Living Disability Within Chinese Female Centenarians: A Cross-Sectional, Complete Sample Study</p>

Abstract: Background and Objective: Activities of daily living (ADL) disability seriously affects the quality of life in the elderly. This study aims to examine the prevalence of ADL disability and its possible correlation with lipid profile indicators (LDL-C, TG and HDL-C) among female centenarians in Hainan, China. Methods: A cross-section of complete sample study including 822 female centenarians was conducted from the China Hainan Centenarians Cohort Study (CHCCS) from June 2014 to December 2016. Barthel index was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Reduced high-density lipoprotein levels were also associated with three GSs, including impaired cognitive function, dependence ADL, and frailty. Other studies have also confirmed that increased levels of high-density lipoproteins have an additional protective effect against dependence in ADL [59]. Notably, no association was found between the GSs and low-density lipoproteins.…”
Section: Discussionmentioning
confidence: 84%
“…Reduced high-density lipoprotein levels were also associated with three GSs, including impaired cognitive function, dependence ADL, and frailty. Other studies have also confirmed that increased levels of high-density lipoproteins have an additional protective effect against dependence in ADL [59]. Notably, no association was found between the GSs and low-density lipoproteins.…”
Section: Discussionmentioning
confidence: 84%
“…However, in an older population, there is no consensus concerning the health impact of hypercholesterolemia on longevity and disability. Studies have shown that higher triglyceride may be related to better ADL among the older population ( 10 , 11 ), and even higher lipid profiles are beneficial to longevity and functional performance among the older population ( 12 15 ). In addition, the influence pathway and physiological mechanism of the possible effect of blood lipids on disability were complex and uncertain.…”
Section: Introductionmentioning
confidence: 99%